Cardiac synchronization and arrhythmia during irreversible electroporation. Issue 3 (1st June 2020) - O'Neill, Conor H.; Martin, Robert C. G.
Abstract: Background and Objectives: Irreversible electroporation (IRE) is a nonthermal electrical tumor ablative strategy for unresectable tumors. IRE is relatively safe around critical structures but may induce cardiac arrhythmia when its delivery is not synchronized to the cardiac cycle. We performed a systematic literature review to determine rates of arrhythmia when IRE was utilized with or without cardiac synchronization. Methods: An online literature search was conducted with additional hand selection of articles. Data were extracted and pooled analyses were performed. Results: Twelve articles were included in analysis. IRE was performed for 481 patients; 46% hepatic tumors (n = 223), 36% pancreatic lesions (n = 168), and multiple other locations including prostate. Synchronization was performed on 422 patients. Arrhythmias were noted in 3.7% of cases (n = 18/481); cardiac synchronization: 1.2% (n = 5/422) vs unsynchronized: 22.0% (n = 13/59), P  < .0001. These events occurred in every organ except the prostate. Conclusions: IRE remains a potent technology for unresectable tumors, but arrhythmia is a clinical concern. This literature review confirms that cardiac gating should be used in all cases outside of prostate to prevent this potentially serious adverse event.